1980
DOI: 10.1002/pssa.2210610229
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dislocation inertia on the thermally activated low-temperature plasticity of materials. I. Theory

Abstract: A method is suggested for taking into account the effect of inertial properties of dislocations on the velocity of their thermally activated motion. The method is based on the results of a statistical analysis of the dislocation motion through a random array of point obstacles. Because of the scatter in geometrical parameters, the dislocations interact with different obstacles at different angles α, even when all the obstacles in the crystal are identical. A fraction of the angles, g, can be higher than the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1981
1981
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…Competition exists at finite temperatures between increased viscous drag contributions that increase the required stress and an activation rate increase that lowers it. Landau derived the effective velocity of dislocations as a function of statistical thermal surmounting of randomly spaced Peierls barriers [56]. The inclusion of this velocity correction term v eff $ ve ÀDH kT ð Þ , where DH is the activation enthalpy estimated to be 0.01 eV and k is the Boltzmann constant, has a minimal effect on the radiation force term, where force is nearly constant with velocity.…”
Section: Resultsmentioning
confidence: 99%
“…Competition exists at finite temperatures between increased viscous drag contributions that increase the required stress and an activation rate increase that lowers it. Landau derived the effective velocity of dislocations as a function of statistical thermal surmounting of randomly spaced Peierls barriers [56]. The inclusion of this velocity correction term v eff $ ve ÀDH kT ð Þ , where DH is the activation enthalpy estimated to be 0.01 eV and k is the Boltzmann constant, has a minimal effect on the radiation force term, where force is nearly constant with velocity.…”
Section: Resultsmentioning
confidence: 99%
“…[9] It was shown that, as distinct from the results of reference, [8] for large concentration of pinning points (L < 10 À7 m) the magnitude of Ds NS is to decrease with increasing concentration of the pinning points. A statistical analysis of the role of the inertia effects in thermally activated dislocation motion [10] led to similar conclusions regarding the dependence of Ds NS on the non-dimensional concentration of the pinning points, C ¼ aS À1/2 , where a is the lattice parameter and S is the average area per pinning point. With growing C, the flow stress increases in both N and S states, leading to a concomitant increase in Ds NS .…”
Section: Introductionmentioning
confidence: 74%
“…For completeness, we note that an effective barrier is not quite the same as a temperature-dependent velocity as originally suggested by Landau [40] (see also [24] and references therein). Note that we are concerned here with the retarding force, rather than the velocity, hence the different form (Fig.…”
Section: Thermally Activated Dislocation Motion With Barriersmentioning
confidence: 92%